Increasing Activeness and Learning Outcomes of Islamic Religious Education Through Strategy Everyone is A Teacher Here - Tugimin (Program Studi Magister Pendidikan IPA, Universitas Mataram, 2022)
This is a classroom action research conducted through 2 cycles or more with each cycle. The stages are planning, action, observation, and reflection. Data collection is done through observation in the classroom and documentation of the results of the actions taken. This classroom action research procedure consists of 4 stages: planning, action, observation, and reflection. The subject material is commendable behavior class XI RPL 1 SMK Negeri 1 Buntok. Results study show strategy of everyone being a teacher here in PAI learning can increase student learning activeness. It can be seen in the increase in student test results in each cycle where in the pre-cycle, the level of completeness is six students or 15.8%, rising to 10 students or 26.3%, increased again in cycle II, namely 17 students or 44.8% and at the end of cycle III to 34 students or 89.5%. This increase was due to improvements in the actions taken by the teacher in each cycle. Strategy everyone is a teacher here in PAI learning can improve student learning outcomes in Class XI RPL 1 SMK Negeri 1 Buntok. This can be seen from the increase in student activity in each cycle. In the first cycle, student activity was in the good and very good categories, there were nine students or 23.6%, rising to 22 students or 57.9%, and at the end of cycle III there were 36 students or 94.7 %. It shows the tendency of students to be active in the learning process. It is proven that students actively listen carefully to the teacher's explanation, is very active in the learning process, have high enthusiasm in exploring material, and are actively involved in group work when given motivation by the teacher in every lesson that is done.